Proline Increases Pigment Production to Improve Oxidative Stress Tolerance and Biocontrol Ability of Metschnikowia citriensis - Liu, Ye; Yi, Lanhua; Ruan, Changqing; Yao, Shixiang; Deng, Lili; Zeng, Kaifang (Frontiers in Microbiology, 2019)
Utilizing antagonistic yeasts is a promising approach for managing postharvest decay of fruits. However, it is well established that various severe stresses encountered in the environment and production process cause the intracellular reactive oxygen species (ROS) accumulation in yeast cells, resulting in cell damage and loss of vitality. Here, proline has been shown to function as a cell protectant and inducer of biofilm formation able to increase the oxidative stress tolerance and the biocontrol ability of the antagonistic yeast Metschnikowia citriensis. Addition of proline to M. citriensis cells induced a significant rise in superoxide dismutase (SOD) and catalase (CAT) activity in the early and late stages of oxidative stress, respectively, and increased the maroon pigment production that directly reduced intracellular iron content and indirectly diminished intracellular ROS levels, and thus inhibited ROS- and iron-induced apoptosis. Treating cells with iron chelator tropolone yielded similar results. Pigment production induced by proline also enhanced the capability of biofilm formation. These results suggested an important role for pigment of M. citriensis in response to oxidative stress. The abilities of proline to scavenge intracellular ROS and inhibit apoptosis, increase pigment production, and promote biofilm formation contribute to the improvements in oxidative stress tolerance and biocontrol efficacy of M. citriensis.